2011
DOI: 10.1053/j.ajkd.2010.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Development and Results of a Kidney Disease Knowledge Survey Given to Patients With CKD

Abstract: Background Little is known about disease specific knowledge in patients with chronic kidney disease (CKD). We developed and examined the results of a survey to characterize kidney disease knowledge. Design Survey about kidney disease knowledge, with questions developed by experts. Setting and Participants: 401 adult patients with CKD (Stages 1–5) attending a nephrology clinic from April to October 2009. Outcomes & Measurements We calculated survey reliability using the Kuder-Richardson-20 coefficient, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
218
6
27

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(267 citation statements)
references
References 51 publications
16
218
6
27
Order By: Relevance
“…9,10 Discordance in our study population ranged from 25% to 50% (depending mostly on patient age), which is consistent with poor recall of treatment details, risks, and benefits conveyed during the informed consent process among patients undergoing medical procedures 11 as well as healthy controls in clinical trials. 12 In addition, our finding that older adults (despite excluding those with dementia) were less likely to report receiving KTPI even when they were informed according to their provider is consistent with the documented age disparity in referral and access to KT.…”
Section: Discussionsupporting
confidence: 72%
“…9,10 Discordance in our study population ranged from 25% to 50% (depending mostly on patient age), which is consistent with poor recall of treatment details, risks, and benefits conveyed during the informed consent process among patients undergoing medical procedures 11 as well as healthy controls in clinical trials. 12 In addition, our finding that older adults (despite excluding those with dementia) were less likely to report receiving KTPI even when they were informed according to their provider is consistent with the documented age disparity in referral and access to KT.…”
Section: Discussionsupporting
confidence: 72%
“…One recent study among patients attending a nephrology clinic identified areas of poor knowledge, allowing investigators to identify subjects on which further patient education should be focused. 27 It is very likely that the profile of CKD knowledge would be different in a population of patients followed up in primary care and that further detailed study would identify areas to target when designing education programmes best suited for those managed in primary care. …”
Section: Implications For Research and Practicementioning
confidence: 99%
“…39 Como pode ser observado na Figura 1, baseado em diversos autores, [39][40][41] os determinantes do LS podem ser agrupados em dois grandes compartimentos que interagem entre si: 1. Os inerentes ao indivíduo; e 2.…”
Section: Determinantes Do Letramento Em Saúdeunclassified